The hope wheel: a model to enable hope-based pedagogy in Climate Change Education - Finnegan, William; d’Abreu, Cathy (Frontiers in Psychology, 2024)
In response to concerns about climate anxiety and distress, researchers and practitioners in both education and psychology have been investigating the importance of engaging climate hope in Climate Change Education (CCE). Synthesizing recent multidisciplinary research, alongside insights from the development of educational programs, this article proposes a new theoretical model for pedagogies of hope in CCE. The Hope Wheel presents three foundational elements: handrails for educators to hold on to while constructively engaging with climate change (honesty, awareness, spaceholding, action), guardrails for educators to be sensitive to when implementing the handrails (climate anxiety, mis-/disinformation, false hope), and lenses to encourage educators to explore connections between complex societal and planetary challenges (complexity, justice, perspectives, creativity, and empathy). This working model aims to support educators by distilling current learnings from the literature into a visual guide. It depicts essential elements to include, as well as avoid, in order to engage honest, hope-oriented CCE for transformative learning in the face of the climate crisis.